2019
DOI: 10.1016/j.neuropsychologia.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Visually evoked responses from the blind field of hemianopic patients

Abstract: Hemianopia is a visual field defect characterized by decreased vision or blindness in the contralesional visual field of both eyes. The presence of well documented above-chance unconscious behavioural responses to visual stimuli presented to the blind hemifield (blindsight) has stimulated a great deal of research on the neural basis of this important phenomenon. The present study is concerned with electrophysiological responses from the blind field. Since previous studies found that transient Visual Evoked Pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…Despite the challenges to uncover the mechanisms mediating awareness (for commentary see Berlucchi et al, 2017), it has been proposed that a fronto-parietal network plays a key role in the processes (Sanchez-Lopez et al, 2017;Passingham and Lau, 2017). Interestingly, this fronto-parietal network is also important for visuospatial attention which can modulate decision criteria and consequently awareness (Vernet et al, 2017).…”
Section: Tablementioning
confidence: 99%
“…Despite the challenges to uncover the mechanisms mediating awareness (for commentary see Berlucchi et al, 2017), it has been proposed that a fronto-parietal network plays a key role in the processes (Sanchez-Lopez et al, 2017;Passingham and Lau, 2017). Interestingly, this fronto-parietal network is also important for visuospatial attention which can modulate decision criteria and consequently awareness (Vernet et al, 2017).…”
Section: Tablementioning
confidence: 99%
“…In visuo-motor tasks after stimulus onset, in addition to the well documented sensorial (P1 and N1) and endogenous (N2 and the P3) components, three more components have been identified: the prefrontal N1, P1 and P2 (pN1, pP1 and pP2 respectively) peaking between 110 and 300 ms after the stimulus onset and localized in the rostral part of anterior insula Sulpizio et al, 2017). While the pN1 and pP1 are related to top-down perceptual processing associated with stimulus physical salience and awareness and sensory-motor integration respectively Sanchez-Lopez et al, 2017), the pP2 has been associated with evidence accumulation process, that is the efficacy of the stimulus-response mapping Darriba & Waszak, 2018;Di Rollo et al, 2016;Perri, Berchicci, Lucci, Spinelli, & Di Russo, 2015b, 2015a. These anterior insular ERP components were recently characterized by the present research group; however, in the past, several research groups found that anterior ERP components were generically localized in frontal areas (Foxe & Simpson, 2002;Potts, Liotti, Tucker, & Posner, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Cortically blind (CB) subjects possess multiple residual visual abilities within their blind field (Mazzi, Savazzi, & Silvanto, 2017;Sanchez-Lopez et al, 2017;Weiskrantz, Warrington, Sanders, & Marshall, 1974). Visual perceptual training in CB fields can further improve performance on trained tasks, even if the subject initially had no residual ability to perform the task, recovering some of the vision lost at the trained locations (Bergsma, Elshout, van der Wildt, & van den Berg, 2012;Bergsma & van der Wildt, 2009;Chokron et al, 2008;Das, Tadin, & Huxlin, 2014;Huxlin et al, 2009;Raemaekers, Bergsma, van Wezel, can der Wildt, & van den Berg, 2011;Raninen, Vanni, Hyvarinen, & Nasanen, 2007;Sahraie et al, 2006;Sahraie et al, 2003;Vaina et al, 2014).…”
Section: Introductionmentioning
confidence: 99%